INNOVATION IN INDUSTRY-BASED LEARNING IN VOCATIONAL EDUCATION: A SYSTEMATIC REVIEW OF BEST PRACTICES IN VARIOUS COUNTRIES AND THEIR RELEVANCE TO INDONESIA - Charnila Desria Heydemans; Syamsul Hadi; Hary Suswanto; Sh Mohd Firdaus; Great Erick Kaumbur (CV. TOTUS TUUS, 2025)
Vocational education plays a crucial role in preparing a skilled workforce for Industry 4.0, which demands technical expertise, critical thinking, and adaptability. Industry-Based Learning (IBL) models, successfully implemented in countries like Germany and Australia, integrate real-world industrial experiences into curricula. However, developing nations, including Indonesia, face challenges such as curriculum-industry misalignment, limited infrastructure, and insufficient industry engagement. This study employs a Systematic Literature Review (SLR) following the PRISMA framework to analyze 26 high-quality articles (2020–2024) on IBL innovations globally. Findings reveal effective models such as non-placement Work-Integrated Learning (WIL), digital competency frameworks, and challenge-based learning, which emphasize industry collaboration and practical skill development. For Indonesia, adapting these approaches—through virtual teaching factories, VR/AR-enhanced training, and dual VET systems—can address geographical and resource constraints. Key recommendations include flexible WIL implementation, digital upskilling for teachers, industry incentives, and policy reforms to align vocational education with labor market needs. The study highlights the need for contextual adaptation of global best practices to enhance Indonesia’s vocational system.